Metal surface antifriction wear-resistant coupling layer and preparation method thereof

By constructing a nitride layer, groove microtexture and sheet lubricating layer on the metal surface, forming a sheet lubricating/microtexture/nitriding coupling layer on the metal surface, the problems of oxidation corrosion and friction wear during the operation process are solved. , achieving good wear resistance and friction resistance.

CN119457452AActive Publication Date: 2025-02-18MATERIAL INST OF CHINA ACADEMY OF ENG PHYSICS
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411608641.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-08
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

During the operation process, metals are prone to oxidation corrosion and frictional wear, resulting in damage to the surface structure and affecting application reliability.

Method used

The nitride layer is constructed on the metal surface by laser, and a grooved microtexture arranged in an array is constructed on the surface of the nitride layer, and then a sheet lubricating layer is constructed on the surface to form metal surface sheet lubrication/microtexture/nitriding Coupling layer.

Benefits of technology

The coupling layer has good wear resistance and corrosion resistance and friction reduction performance, which can effectively protect the metal surface, improve its friction and wear resistance, and maintain a stable friction reduction effect under long-term wear conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457452A_ABST
    Figure CN119457452A_ABST
Patent Text Reader

Abstract

The invention discloses a metal surface antifriction wear-resistant coupling layer and a preparation method thereof. The preparation method comprises the following steps: step 1, constructing a nitride layer on a metal surface by using laser; step 2, constructing groove microtextures arranged in an array on the surface of the nitride layer in the step 1; and (3) a lamellar lubricating layer is constructed on the surface of the groove micro-texture in the step (2), and the metal surface lamellar lubricating / micro-texture / nitriding coupling layer is obtained. According to the method, laser nitriding, surface micro-texture treatment and solid lubrication treatment are sequentially carried out on the surface of the metal base material, a nano lubrication / micro-texture / nitriding antifriction and wear-resistant coupling layer is constructed on the surface of the metal base material, the surface of the metal base material can be endowed with long-acting antifriction, wear resistance and corrosion resistance, and the method is an excellent metal base material surface protection technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface wear-resistant function modification, and in particular to a metal surface friction-reducing and wear-resistant coupling layer and a preparation method thereof. Background Art

[0002] At present, the commonly used methods in the field of metal surface wear-resistant functional modification include metal surface coating treatment, metal surface alloying treatment, metal surface structure design and other technologies.

[0003] Metal surface coating treatment generally involves coating the metal surface with relatively stable organic polymer materials or inorganic lubricating materials, such as epoxy resin, molybdenum disulfide, etc. This technology is convenient and fast, and can quickly form a protective cushion layer on the metal surface to prevent external punching and friction from causing wear on the metal substrate. However, since organic polymer materials generally contain more active groups such as hydroxyl or carbonyl groups, the coating is prone to aging during use, and it is very easy to fall off the metal surface during complex wear processes, ultimately leading to protection failure. Although the lamellar sliding effect of inorganic lubricating materials can effectively reduce the friction coefficient, it often needs to reach a certain thickness to exert a stable friction reduction effect. Under severe vibration conditions, it is difficult for it to exist stably on the surface of the metal substrate for a long time.

[0004] Metal surface alloying treatment refers to the use of laser surface alloying, pulsed laser deposition, magnetron sputtering and other technologies to melt or deposit a layer of alloying elements on the metal surface to protect the metal surface. The alloy coating formed by this technology has relatively good bonding with the metal substrate and has an ideal metal protection effect. However, the conditions required for metal surface alloying treatment are relatively harsh. Some technologies need to be operated under a specific inert gas environment and pressure, which has high requirements for equipment and operators, limited efficiency, and high operating costs. In addition, it is difficult to effectively reduce the friction of metal uranium by only forming a micron-level alloying layer on the metal surface. Under long-term wear conditions, the alloying layer is easily damaged by wear.

[0005] Metal surface structure design is to design a certain microstructure on the metal surface by using pulsed laser, ultrasonic rolling or heat treatment technology or to achieve phase change strengthening through grain refinement. This design cleverly uses the micro-texture friction reduction mechanism or the idea of ​​metal's own phase change strengthening to achieve good wear-resistant protection without affecting the metal surface composition. However, this type of technology has limited protective performance. Although the modified metal surface has a certain improvement in wear resistance, the hardness characteristics of the substrate itself will greatly determine the structural stability of the structure. Under strong punching friction, the surface structure is easily damaged by wear.

[0006] The surface wear resistance of precision metal devices with high added value will greatly affect their reliability in engineering applications, such as precision bearings in aerospace, artificial joints and bones in the medical field, or uranium materials in the nuclear industry. Among them, metallic uranium is widely used in the nuclear industry and other fields due to its unique nuclear properties. However, due to the complexity and diversity of the use environment, it is very easy to have problems such as oxidation corrosion and friction and wear during service, resulting in damage to its surface structure, which will threaten its application reliability in severe cases. Constructing a surface passivation layer can effectively reduce the oxidation corrosion of the metal. However, during service, the passivation layer is easily damaged by friction and wear and fails. Based on this, the development of a friction-reducing and wear-resistant functional layer will greatly improve the reliability of metallic uranium applications. Summary of the invention

[0007] The invention aims to solve the problems of oxidation corrosion and friction wear that easily occur to metals during use, and provides a friction-reducing and wear-resistant coupling layer on a metal surface and a preparation method thereof.

[0008] In order to achieve the above technical objectives, the technical solution provided by the present invention is:

[0009] A method for preparing a friction-reducing and wear-resistant coupling layer on a metal surface comprises the following steps:

[0010] Step 1: Use laser to build a nitride layer on the metal surface;

[0011] Step 2: constructing a groove micro-texture arranged in an array on the surface of the nitride layer in step 1;

[0012] Step 3: construct a lamellar lubrication layer on the surface of the groove microtexture in step 2 to obtain a metal surface lamellar lubrication / microtexture / nitridation coupling layer.

[0013] Furthermore, in step 1, the specific steps include: constructing a nitride layer on the uranium surface using a laser in a nitrogen atmosphere.

[0014] Furthermore, the nitrogen atmosphere is 1 to 3 atmospheres, the laser output power is 10 to 60 W, the scanning speed is 50 to 100 mm / s, and the scanning step length is 0.3 to 1.0 mm.

[0015] Furthermore, in step 2, the specific steps include: using a marking machine to construct a groove micro-texture on the metal surface by adjusting the laser beam efficiency, frequency, scanning speed, and path.

[0016] Furthermore, the laser beam efficiency is 10% to 30%, the frequency is 15 to 40 kHz, and the scanning speed is 500 to 15000 mm / s.

[0017] Furthermore, the groove has a diameter of 100-150 μm and a depth of 0.2-1.0 μm.

[0018] Furthermore, the lamellar lubricating layer adopts a solid lubricant, and the solid lubricant is any one of molybdenum disulfide, tungsten disulfide, and graphene.

[0019] Furthermore, the solid lubricant powder is evenly coated on the surface of the uranium substrate, and the coating amount is 0.01-0.05 g / cm 2 .

[0020] The present invention also provides a friction-reducing and wear-resistant coupling layer on a metal surface, which is prepared by the above method.

[0021] The present invention has the following beneficial effects:

[0022] 1. It is difficult to make the metal substrate chemically inert by metal surface coating treatment and metal surface structure design, and corrosion and wear are prone to occur during the wear process. The coupling layer prepared by the present invention has good wear resistance and corrosion resistance. The reason is that the bottom layer of the prepared coupling layer is a nitride layer with high hardness, so it can effectively protect the microtexture. In addition, the nitride layer has stable chemical properties and has extremely strong corrosion resistance in the atmospheric environment.

[0023] 2. The metal surface alloying technology and surface structure design give the substrate limited friction reduction performance. During use, it is very easy to be worn and fail, thereby accelerating the corrosion and wear of the uranium substrate. The coupling layer prepared by the present invention has excellent friction reduction. The reason is that the solid lubricating material on the surface of the prepared coupling layer can effectively reduce the friction coefficient, thereby reducing the punching friction damage and improving the friction and wear resistance of the substrate.

[0024] 3. The friction-reducing and wear-resistant protective layer prepared by metal surface coating treatment is difficult to stably exist on the surface of the uranium substrate and is easy to deteriorate the physical and chemical properties of the uranium substrate; the metal surface structure design is difficult to give the surface an extremely low friction coefficient, and the hardness improvement value is limited; the friction-reducing performance provided by the metal surface alloying technology is limited. The friction-reducing and wear-resistant performance of the coupling layer prepared by the present invention is stable, and the solid lubricating material on the surface of the prepared coupling layer is stored in a large amount in the surface micro-texture. During the friction and wear process, it can be continuously replenished from the micro-texture grooves between the friction pairs. In addition, the harder nitride layer can also effectively protect the micro-texture. Therefore, the coupling layer has stable friction-reducing and wear-resistant properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the wear-reducing and coupling-resistant layer on the surface of metal uranium and its preparation process;

[0026] Figure 2 is the wear resistance diagram of the sample after only laser nitriding and microtexturing treatment;

[0027] Figure 3Scanning electron microscope images of uranium samples after modification in (a) untreated; U, (b) laser nitriding: U-LSN, (c) nitriding / microtexture: U-LSN / T, (d) nitriding / microtexture / solid lubrication: U-LSN / TL; (e) data diagram of the change of friction coefficient of uranium substrate surface under different conditions under 2N load;

[0028] Figure 4 The SEM and EDS data after wear test. (a) Original uranium sample, (b) Surface nitridation / microtexture: U-LSN / T, (d) Surface nitridation / microtexture / solid lubrication: U-LSN / TL. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0031] like Figure 1 As shown, a method for preparing a friction-reducing and wear-resistant coupling layer on a metal surface comprises the following steps:

[0032] Step 1: Use a laser to build a nitride layer on the metal surface.

[0033] Specifically, in step 1, the specific steps include: constructing a nitride layer on the uranium surface using a laser under a nitrogen pressure range of 1 to 3 atmospheres (0.1 atm≈1 atmosphere), wherein the laser output power is 10 to 60 W, the scanning speed is 50 to 100 mm / s, and the scanning step length is 0.3 to 1.0 mm.

[0034] Step 2: constructing an array-arranged groove micro-texture on the surface of the nitride layer in step 1.

[0035] Specifically, in step 2, the specific steps include: using a marking machine to construct a groove micro-texture on the metal surface by adjusting the laser beam efficiency, frequency, scanning speed, and path; wherein the laser beam efficiency is 10% to 30%, the frequency is 15 to 40 kHz, and the scanning speed is 500 to 15000 mm / s. The groove diameter is 100 to 150 μm, the depth is 0.2 to 1.0 μm, and the groove shape is a concave pit, including but not limited to other surface micro-textures that can store certain mesoporous silicon balls and lubricants, such as grooves, triangles, rectangles, grids, etc.; in addition, according to Figure 2As shown in the figure, after micro-texturing treatment, the highest point of the edge of the micro-dimple does not exceed 3μm, thereby avoiding the increase of metal surface roughness due to edge protrusion and ensuring that the micro-dimple can store a large amount of lubricating materials and abrasive particles and debris.

[0036] Step 3: construct a lamellar lubrication layer on the surface of the groove microtexture in step 2 to obtain a uranium surface lamellar lubrication / microtexture / nitridation coupling layer.

[0037] Specifically, the lamellar lubricating layer adopts a solid lubricant, and the solid lubricant is any one of molybdenum disulfide, tungsten disulfide, and graphene. The solid lubricant powder is evenly coated on the surface of the uranium substrate, and the coating amount is 0.01-0.05 g / cm 2 .

[0038] Example 1

[0039] Step 1: First, clean the uranium substrate with acetone and ethanol, place it in a sealed chamber, and then in a 0.1atm nitrogen atmosphere, control the laser output power to 60W, the scanning speed to 100mm / s, and the scanning step length to 0.5mm to build a nitride layer on the surface of the uranium substrate.

[0040] Step 2: After cleaning, place the laser nitrided uranium sample in a sealed chamber. In a low-oxygen and low-humidity atmosphere, control the marking machine efficiency to 10%, the frequency to 25kHz, the scanning speed to 10000mm / s, and perform a zigzag scanning to construct a groove microtexture on the surface of the nitrided layer.

[0041] Step 3: After the surface microtextured uranium sample was polished with 1200 mesh and 2500 mesh sandpaper, it was cleaned and dried. Then, molybdenum disulfide powder was evenly rubbed on the surface of the uranium substrate (0.01 g / cm 2 ).

[0042] Example 2

[0043] Step 1: First, the uranium substrate is cleaned with acetone and ethanol and placed in a sealed chamber. Then, in a 0.3atm nitrogen atmosphere, the laser output power is controlled to 10W, the scanning speed is 50mm / s, and the scanning step length is 0.3mm to construct a nitride layer on the surface of the uranium substrate.

[0044] Step 2: After cleaning, place the laser nitrided uranium sample in a sealed chamber. In a low-oxygen and low-humidity atmosphere, control the marking machine efficiency to 30%, the frequency to 15 kHz, the scanning speed to 500 mm / s, and perform reciprocating scanning to construct a groove microtexture on the surface of the nitrided layer.

[0045] Step 3: After the surface microtextured uranium sample was polished with 1200 mesh and 2500 mesh sandpaper, it was cleaned and dried. Then, tungsten disulfide powder was evenly rubbed on the surface of the uranium substrate (0.03 g / cm2 ).

[0046] Example 3

[0047] Step 1: First, the uranium substrate is cleaned with acetone and ethanol and placed in a sealed chamber. Then, in a 0.3atm nitrogen atmosphere, the laser output power is controlled to 30W, the scanning speed is 70mm / s, and the scanning step length is 0.6mm to construct a nitride layer on the surface of the uranium substrate.

[0048] Step 2: After cleaning, place the laser nitrided uranium sample in a sealed chamber. In a low-oxygen and low-humidity atmosphere, control the marking machine efficiency to 30%, the frequency to 15 kHz, the scanning speed to 500 mm / s, and perform reciprocating scanning to construct a groove microtexture on the surface of the nitrided layer.

[0049] Step 3: After the surface microtextured uranium sample was polished with 1200 mesh and 2500 mesh sandpaper, it was cleaned and dried, and the graphene powder was evenly rubbed on the surface of the uranium substrate by rubbing method (0.02g / cm 2 ).

[0050] Example 1 is used as the research and analysis object, and the effects of the other embodiments are similar to those of Example 1. Figure 2 As shown in a, b, and c, the wear resistance of the nitride layer and the microtexture was investigated through the ring-block wear test. The study found that under a relatively small load (1N), the nitride layer will wear to a certain extent, and the friction coefficient will quickly stabilize at about 0.78. During the experiment, a sharp and harsh sound due to friction lasts for about 10 seconds. Under a relatively large load (2N), the surface of the nitride layer will wear seriously, and the friction coefficient is in a relatively large fluctuation state (0.6-0.75). During the experiment, a sharp and harsh sound caused by the instability of the wear interface lasts for up to 300 seconds, and the nitride layer peels off in pieces. The surface of the uranium nitride sample after wear was analyzed by SEM and EDS. It was found that compared with the large amount of nitrogen in the unworn area (Area2, N: 7.35wt%, O: 2.25wt%), the nitrogen content in the worn area (Area1, N: 2.89wt%, O: 20.23wt%; Area3, N: 2.52wt%, O: 24.4wt%; Area4, N: 2.1wt%, O: 16.14wt%) was significantly reduced, and the mass proportion of oxygen in the worn area was significantly increased, indicating that a certain amount of corrosive wear occurred in the worn area. Compared with wear areas 1 and 3, in wear area 4, it can be found that the silicon and oxygen content are significantly lower. Combined with SEM, it can be judged that the degree of corrosive wear in this area is relatively light. Figure 2 d and Figure 2As shown in Figure e, the U-LSN / T sample was subjected to a wear test under a load of 2N. Through SEM, it can be found that the micro-texture modification did not significantly improve the wear resistance of the substrate, and obvious wear marks can still be seen. Compared with the area without severe wear, there is still a certain nitride layer (Area3, N: 7.54wt%, O: 7.31wt%), and the adhesive wear area has more serious corrosion wear (Area2, N: 1.45wt%, O: 28.58wt%). The micro-texture morphology at the wear mark is also destroyed due to wear. There is a certain amount of nitrogen at the center point of the micro-texture area (Area1, N: 3.87wt%, O: 2.78wt%), which also shows that the prepared micro-texture still has a certain nitride layer in the bottom area of ​​the micro-pits. In addition, since the thickness of the prepared nitride layer is relatively thin, nanoindentation is used to characterize the influence of the nitride layer on the hardness of the substrate. The study found that laser surface nitriding can increase the hardness of the uranium substrate from 4GPa to about 7.5GPa, significantly improving the surface hardness of the substrate ( Figure 2 f). The above experimental results show that although the presence of the nitride layer and micro-texture can improve the hardness of the substrate and enhance the wear resistance to a certain extent, under a larger load (2N), the modified layer will still suffer severe wear.

[0051] Figure 3 The surface scanning electron microscope images of the uranium substrate after different treatments are shown in Figure 2. Figure 3 As shown in (a), the surface of the untreated uranium substrate is relatively smooth after sandpaper polishing, but there are still some protrusions; after laser nitriding treatment, the surface is smoother ( Figure 3 b); After the nitrided sample was treated with microtexture, regularly arranged micro-dimples appeared on the surface ( Figure 3 c); Finally, after a layer of molybdenum disulfide (black) is coated on the surface of the modified uranium substrate, the micro-dimples appear black, indicating that a certain amount of lamellar lubricating material is stored in them ( Figure 3 c) Pin-on-disc wear test was used to further characterize the friction reduction and wear resistance of the coupling layer. During the experiment, the black friction pair was Si 3 N 4 The ball has a load of 2N, a radius of 2.8mm, and the number of friction circles is set to 2000. Figure 3 As shown by the black line in (e), the friction coefficient of the untreated uranium substrate surface increases rapidly to above 0.4 at the beginning of friction, followed by violent shaking, a harsh friction sound during the experiment, and finally the friction coefficient remains at around 0.5-0.6; Figure 3 As shown by the red line in (e), the uranium sample after laser nitridation reaches above 0.5 more quickly at the beginning of friction under a larger load of 2N, and also emits a sharp friction sound during the experiment, and finally the friction coefficient stabilizes at around 0.7; Figure 3As shown by the blue line in (e), the sample after nitriding / microtexture has a certain effect of storing wear debris in the early stage due to the existence of microtexture, but due to the large load, the microtexture is quickly destroyed, thus losing the friction reduction performance, causing the friction coefficient to increase rapidly and finally stabilize at around 0.7; compared with the wear experiments of the first three, the sample after nitriding / microtexture / solid lubrication has no sharp wear sound during the experiment, such as Figure 3 As shown by the pink line in (e), the friction coefficient is always stable below 0.1, which shows that the designed coupling layer can achieve excellent friction reduction and wear resistance. In addition, the necessity of micro-texture is verified by comparison. The sample without micro-texture treatment only contains nitrided and solid lubricated surfaces, and its friction reduction performance is limited. During the wear process, the friction coefficient is higher than 0.1, which is worse than the friction reduction effect of the coupling layer containing micro-texture.

[0052] In order to further characterize the friction reduction and wear resistance of the coupling layer, the surface morphology and elements after wear were analyzed using scanning electron microscopy and energy spectrum scanning. Figure 4 As shown in (a), the wear scar area is deep and contains a large amount of Si and O elements. This is because the Si element in the grinding pair wears on the surface of the metal uranium substrate, and oxidation wear occurs during the wear process. The uranium substrate treated with nitriding / microtexture / solid lubrication has been subjected to a 35m cyclic wear test. Figure 4 As shown in (c), there is no obvious wear at the wear scar, and the micro-dimple structure still exists, with a small amount of molybdenum disulfide inside. There is no silicon element in the wear scar area, but there is a certain amount of N element (the nitride layer is exposed but not damaged by wear), which indicates that the coupling layer can effectively reduce wear and exert an excellent friction reduction effect.

[0053] In summary, the present invention constructs a friction-reducing and wear-resistant coupling layer of nano-lubrication / micro-texturing / nitridation on the surface of the uranium substrate by successively performing laser nitriding, surface micro-texturing treatment, and solid lubrication treatment on the surface of the uranium substrate, which can give the surface of the uranium substrate long-term friction-reducing, wear-resistant and corrosion-resistant properties, and is an excellent uranium substrate surface protection technology.

[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0055] The above specific implementation methods are detailed descriptions of the present invention. It cannot be determined that the specific implementation methods of the present invention are limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions and substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A method for preparing a friction-reducing and wear-resistant coupling layer on a metal surface, characterized in that: The steps include: Step 1: Use laser to build a nitride layer on the metal surface; Step 2: constructing a groove micro-texture arranged in an array on the surface of the nitride layer in step 1; Step 3: construct a lamellar lubrication layer on the surface of the groove microtexture in step 2 to obtain a metal surface lamellar lubrication / microtexture / nitridation coupling layer.

2. The method for preparing a friction-reducing and wear-resistant coupling layer on a metal surface according to claim 1, characterized in that: In step 1, the specific steps include: constructing a nitride layer on the metal surface using a laser in a nitrogen atmosphere.

3. The method for preparing a friction-reducing and wear-resistant coupling layer on a metal surface according to claim 2, characterized in that: The nitrogen atmosphere is 1 to 3 atmospheres, the laser output power is 10 to 60 W, the scanning speed is 50 to 100 mm / s, and the scanning step length is 0.3 to 1.0 mm.

4. The method for preparing a friction-reducing and wear-resistant coupling layer on a metal surface according to claim 1, characterized in that: In step 2, the specific steps include: using a marking machine to construct a groove micro-texture on the metal surface by adjusting the laser beam efficiency, frequency, scanning speed, and path.

5. The method for preparing a special surface friction reducing and wear resistant coupling layer according to claim 4, characterized in that: The laser beam efficiency is 10% to 30%, the frequency is 15 to 40 kHz, and the scanning speed is 500 to 15000 mm / s.

6. The method for preparing a friction-reducing and wear-resistant coupling layer on a metal surface according to claim 4, characterized in that: The groove has a diameter of 100-150 μm and a depth of 0.2-1.0 μm.

7. The method for preparing a friction-reducing and wear-resistant coupling layer on a metal surface according to claim 1, characterized in that: The sheet lubricating layer adopts a solid lubricant, and the solid lubricant is any one of molybdenum disulfide, tungsten disulfide and graphene.

8. The method for preparing a friction-reducing and wear-resistant coupling layer on a metal surface according to claim 7, characterized in that: The solid lubricant powder is evenly coated on the surface of the metal substrate, and the coating amount is 0.01-0.05 g / cm 2 .

9. A friction-reducing and wear-resistant coupling layer on a metal surface, characterized in that: The method is prepared by any one of claims 1 to 8.

Citation Information

Patent Citations

  • Combined compressor wear-resistant piston ring

    CN103696948A

  • Method for enhancing laser nitridation effect through double-pulse stepped waveform laser

    CN103789720A

  • Method and device for preparing uranium surface anti-corrosion protecting layer through atmospheric laser passivation

    CN105063547A

  • Preparation method for micro-nano textured titanium nitride solid lubricant film

    CN105088129A

  • Siliconizing modified layer on surface of metal uranium and preparation method and preparation device thereof

    CN109097725A